Soft and hard tissue changes after compensatory treatment in skeletal class III malocclusion - Lijuan Liu; Yuting Liu; Kai Guo; Haojie Ma; Fanghong Yang (PLoS ONE, 2025)
Background The camouflage treatment of skeletal class III malocclusion can include both premolar extraction and mandibular third molar extraction-based approaches. This study aimed to compare an all four second premolar extraction approach with a mandibular third molar extraction and temporary anchorage devices (TADs)-based approach for compensatory orthodontic treatment in mild to moderate skeletal class III malocclusion. Methods 31 subjects (mean age = 19.65 ± 3.91 years, male = 12, female = 19) with skeletal class III malocclusion were included in this retrospective, observational study. Lateral cephalograms taken before and after treatment were used to perform measurements for 7 dental indicators, 9 skeletal indicators, and 5 soft tissue indicators. Statistical analyses were performed to compare the cephalometric measurements between groups. Results The patients’ profiles were improved after treatment, and molars reached a neutral occlusal relationship. Dental cephalometric measurements showed that mandibular incisor to mandibular plane angle (IMPA) (-7.73 ± 4.72°), lower incisor–Nasion–B point angle (L1-NB angle) (-8.36 ± 4.57°),and the lower incisor–Nasion–B point distance (L1-NB distance) (-2.02 ± 1.42 mm) all significantly reduced (P < 0.05) in the premolar extraction group, while the changes were non-significant in the mandibular third molar extraction group, and the between-group differences were significant. The angle between the long axis of upper incisors and that of lower incisors (U1-L1) increased significantly (7.76 ± 8.55°) in the premolar extraction group but decreased significantly in the mandibular third molar extraction group (-4.64 ± 5.96°) (P < 0.05). Skeletal cephalometric measurements showed that Sella–Nasion–B point angle (SNB), decreased (premolar extraction group: -1.43 ± 0.87°, mandibular third molar extraction group: -0.71 ± 0.73°), A point–Nasion–B point angle (ANB) increased (premolar extraction group: 1.01 ± 0.86°, mandibular third molar extraction group: 1.22 ± 0.93°) and Wits increased (premolar extraction group: 1.39 ± 0.93 mm, mandibular third molar extraction group: 1.00 ± 0.60 mm) significantly in both groups, P < 0.05; with a significantly larger decrease in SNB in the premolar extraction group (P < 0.05). Soft tissue measurement items showed lower lip eversion (LL-E) decreased (premolar extraction group: 1.77 ± 1.61 mm, mandibular third molar extraction group: 0.76 ± 1.14 mm) and Lip Difference increased (premolar extraction group: 2.30 ± 0.58 mm, mandibular third molar extraction group: (2.01 ± 0.52 mm) significantly in both groups (P < 0.05), with between-group differences non-significant. Analysis of co-variance accounting for the pre-treatment values as the covariate, showed significant effects of the treatment group for the parameters IMPA, L1-NB (mm), L1-NB (°), U1-L1(°), SNA, SNB, and Wits value. Conclusion For mild and moderate skeletal class III malocclusion patients, both premolar extraction and mandibular third molar extraction with TAD-based approaches showed good clinical outcomes. The premolar extraction group showed greater SNB angle and compensatory lingual inclination of the lower incisors, along with significant reduction in OP-SN angle in the mandibular third molar extraction group, which contributed to the counterclockwise movement of the occlusal plane. Soft tissue changes mainly included improvements in lower lip protrusion with no significant differences noted between the two groups.